2011
DOI: 10.1039/c1ob05261f
|View full text |Cite
|
Sign up to set email alerts
|

DPO and POPOP carboxylate-analog sensors by sequential palladium-catalysed direct arylation of oxazole-4-carboxylates

Abstract: Sequential palladium-catalysed direct (het)arylation of oxazole-4-carboxylates is achieved to give rapid access to DPO and POPOP (di)carboxylate-analogs. Three novel DPO- and POPOP-type sensors with unusual Stokes shifts and high quantum yields are discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Two novel sensors were identified with a two- and three-fold Stokes shift as compared to their DPO (diphenyloxazole) and POPOP (phenyloxazolephenyloxazolephenyl) references, and with high quantum yields (Scheme 11) [53]. …”
Section: Reviewmentioning
confidence: 99%
“…Two novel sensors were identified with a two- and three-fold Stokes shift as compared to their DPO (diphenyloxazole) and POPOP (phenyloxazolephenyloxazolephenyl) references, and with high quantum yields (Scheme 11) [53]. …”
Section: Reviewmentioning
confidence: 99%
“…Organic molecules emitting light in various spectral regions are widely used in many fields of science and technology. Among them are aryl-substituted oxazoles, which are highly efficient violet or blue emitting luminophores [1,2]. A burst of interest towards this class of materials was triggered by their applicability as activators and spectral shifters in liquid and plastic scintillators detecting elementary particles and ionizing radiation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, symmetrically 2,5-disubstituted compounds 124a and 124b were synthesized in 80 and 78% yields, 66 respectively, via bis-arylation of compounds 51h and 51i with two equivalents of 1-iodo-4-(trifluoromethyl)benzene (123) in DMA at 150°C in the presence of Cs 2 CO 3 as the base and a catalytic amount of Pd(phen) 2 (PF 6 ) 2 (Scheme 31). 67 In concluding this section, it should be noted that Bíró and Kotschy investigated the Pd(OAc) 2 /PCy 3 -catalyzed arylation of α,α-diphenylbenzo [b]thiophene-3-methanol (125) and, in contrast the results previously observed by Miura and co-workers for the arylation reaction of α,α-dimethylbenzo [b]thiophene-3-methanol (64), 47 they found that the reaction of 125 with two equivalents of aryl bromide in oxylene at 110°C in the presence of Cs 2 CO 3 (2 equiv) usually led to the concomitant formation of 3-arylbenzo [b]thiophenes 126 and 2,3-diarylbenzo [b]thiophenes 65, although in many cases the major products were the ipso-coupled 3-aryl derivatives 126 (Scheme 32). 68 Nevertheless, the reaction of 125 with 1-chloro-2-fluorobenzene (127) led to 2,3-bis(2-fluorophenyl)ben- zo [b]thiophene (65d) ( Figure 14) in 100% GLC yield and 51% isolated yield.…”
Section: Figure 13mentioning
confidence: 99%
“…The synthesis of compounds 227 and 230, two highly luminescent 2,5-diaryloxazoles with unusual Stokes shifts, was accomplished by Hoarau and co-workers through palladium-catalyzed C2 arylation of the corresponding 4ethoxycarbonyl-substituted 5-aryloxazoles 225 and 228, respectively. 125…”
Section: Scheme 72mentioning
confidence: 99%